2016
DOI: 10.1111/jace.14148
|View full text |Cite
|
Sign up to set email alerts
|

Mullite–Nickel Magnetic Nanocomposite Fibers Obtained from Electrospinning Followed by Thermal Reduction

Abstract: Mullite-nickel nanocomposite fibers with Ni nanoparticles of controllable size, dispersion, and consequent magnetic properties were fabricated using sol-gel/electrospinning method, followed by thermal reduction. The fibers were electrospun from an aqueous solution containing sol-gel mullite precursor and nickel nitrate. These fibers were then heat treated in the reducing atmosphere between 550°C and 750°C to achieve fine-dis persed metallic Ni nanoparticles (NPs). After the Ni 2+ was reduced to Ni NPs at 750°C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 72 publications
(109 reference statements)
0
5
0
Order By: Relevance
“…124 The calcination conditions are adapted to meet the varying demands of a given system. For example, air is an idealised atmosphere if metal oxide NFs 125 are targeted, whereas hydrogen (H 2 ), [126][127][128] often in combination with an inert gas such as argon (Ar), [129][130][131][132] and ammonia gas (NH 3 ) are adopted as a reduction (often referred to as de-oxidation in the literature) source. In some cases, the calcination atmosphere is selected to generate oxygen vacancies or eliminate impure phases.…”
Section: Product Morphology and Corresponding Processingmentioning
confidence: 99%
See 1 more Smart Citation
“…124 The calcination conditions are adapted to meet the varying demands of a given system. For example, air is an idealised atmosphere if metal oxide NFs 125 are targeted, whereas hydrogen (H 2 ), [126][127][128] often in combination with an inert gas such as argon (Ar), [129][130][131][132] and ammonia gas (NH 3 ) are adopted as a reduction (often referred to as de-oxidation in the literature) source. In some cases, the calcination atmosphere is selected to generate oxygen vacancies or eliminate impure phases.…”
Section: Product Morphology and Corresponding Processingmentioning
confidence: 99%
“…Generally, for a given system, lower thermal treatment temperatures result in smaller particles being formed (down to a critical minimum size) and the smaller particles exhibit smaller M s values. 106,114,119,122,132,133,170,172,[176][177][178][179][180][181][182][183][184][185][186][187][188] Larger particles have less magnetic contribution from the surface (whilst the contribution from the interior concomitantly increases) and thus the M s value increases. 114 However, the smaller M s values observed at low calcination temperatures are not always only due to the decrease in size of the particles.…”
Section: Processing Parameters and Magnetic Propertiesmentioning
confidence: 99%
“…In recent years, polymeric nanocomposites embedded nanoparticles with properties of electricity and magnetism have attracted the great interest of many researchers due to their wide applications in biomedical [1,2], electrochemical [3], microwave absorption [4], and optical materials [5]. Electrospinning (ES) is an efficient method for the fabrication of magnetic composite nanofibers (MCNF) [6]. However, the obtained nanocomposites usually show random structures, which could not satisfy the application requirement.…”
Section: Introductionmentioning
confidence: 99%
“…5,14,24,25 Recent studies demonstrated a robust and attractive methodology to make many desirable fillers magnetic by decorating ceramic particles with magnetic nanoparticles responding to sufficiently weak magnetic fields. 14,26,32 We will follow this methodology.…”
Section: Introductionmentioning
confidence: 99%